Collaboration and innovation in criminal justice: an activity theory alternative to offender rehabilitation - Rocha, Paulo (Routledge frontiers of criminal justice, 2022)
Introduction: Understanding Offender Rehabilitation -- Theoretical Framework: Activity Theory and Innovation in The Public Sector -- Empirical Evidence: A Detailed Case Study of A Successful Alternative to Imprisonment -- Moving The State of The Art Forward: Suggestions on CO-created Alternatives to Imprisonment as a Means to Rehabilitate Offenders in The Community -- Final Remarks.